2018
DOI: 10.1109/tap.2018.2809492
|View full text |Cite
|
Sign up to set email alerts
|

Low Cross-Polarization Vivaldi Arrays

Abstract: ACKNOWLEDGMENTSI would like to begin by extending my gratitude for having the opportunity and privilege to study under the guidance of my advisor, Prof. Marinos Vouvakis, over the course of five years for my Master's and PhD research. His energy, drive, and motivation to not only teach but also to stimulate critical thinking, to invoke a practical mindset, and to create with meaning have left me with invaluable principles. I am indebted to him for challenging me and his endless patience and support throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 100 publications
0
28
0
Order By: Relevance
“…2 shows the simulated Γ < − 10 dB for TSA (without grooves) shown as a dotted line over FBW∼0.59 (1.1-2.0 GHz). The fact that the x-pol level in TSAs is higher and even more severe while scanning is illustrated in the vast literature [3,[13][14][15][16][17][18][19][20][21]. The present study provides a solution to suppress the x-pol level by the virtue of TSA's geometry modification.…”
Section: Gtsa Design With Groovesmentioning
confidence: 77%
See 3 more Smart Citations
“…2 shows the simulated Γ < − 10 dB for TSA (without grooves) shown as a dotted line over FBW∼0.59 (1.1-2.0 GHz). The fact that the x-pol level in TSAs is higher and even more severe while scanning is illustrated in the vast literature [3,[13][14][15][16][17][18][19][20][21]. The present study provides a solution to suppress the x-pol level by the virtue of TSA's geometry modification.…”
Section: Gtsa Design With Groovesmentioning
confidence: 77%
“…Nalumakkal et al [20] showed the measured low x-pol <−20 dB at the broad side, which increased to higher values of the order of −5 to −10 dB at scan angles farther than 20° from the broad side. Logan et al [21] have shown x-pol <−25 dB over a larger scan volume than 45°. The present work complements the existing approaches for the design and realisation of wide scan and wide band TSA element/TSA arrays with low levels of x-pol at the broad side and also during scanning in non-principal planes as well.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Among UWB arrays, the tapered slot or Vivaldi arrays are known for their broad >10:1 impedance bandwidths, but are typically large in size with poor polarisation purity [2]. To address the polarisation purity, recent Vivaldi variants, known as the sliced notch antenna array, compensate for the imbalanced current potentials on the Vivaldi fin edges [3].…”
Section: Introductionmentioning
confidence: 99%